College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter 5, Systems of Equations and Inequalities - Section 5.2 - Systems of Linear Equations in Several Variables - 5.2 Exercises - Page 455: 8



Work Step by Step

Given: $3x-3y+z=0; y+4z=10; z=3$ Plug $z=3$ in the second equation. we get $y+4(3)=10 \implies y=-2$ Now, Plug $y=-2,z=3$ in the first equation. we have $3x-3(-2)+(3)=0$ or, $3x=-9 \implies x=-3$ Hence, the solution is:$(x,y,z)=(-3,-2,3)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.